2015
DOI: 10.1039/c5ra02016f
|View full text |Cite
|
Sign up to set email alerts
|

P34HB film promotes cell adhesion, in vitro proliferation, and in vivo cartilage repair

Abstract: The management of chondral defects is a challenging topic of current interest for scientists and surgeons, which has a crucial impact on human cost. Even after several centuries after its first observation, this problem has still not found a satisfactory and definitive answer. Cartilage tissue engineering, which involves novel natural scaffolds, has emerged as a promising strategy for cartilage regeneration and repair. In this study, bio-plasticpoly-3-hydroxybutyrate-4-hydroxybutyrate (P34HB) film was first fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Variable-controlling method was adopted to readjust technique parameters based on our previous study on pure P34HB. 24 Fabrication was performed in a hood with dry air convection (23−27 °C, 35−45% relative humidity). The electrospun solution was pumped by a 10 mL syringe with a 21-G metallic needle (0.81 and 0.54 mm for outer and internal diameter).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Variable-controlling method was adopted to readjust technique parameters based on our previous study on pure P34HB. 24 Fabrication was performed in a hood with dry air convection (23−27 °C, 35−45% relative humidity). The electrospun solution was pumped by a 10 mL syringe with a 21-G metallic needle (0.81 and 0.54 mm for outer and internal diameter).…”
Section: Methodsmentioning
confidence: 99%
“…23−27 Our group also conducted studies on its properties in different fields. 24,25,28,29 Fu et al compared two types of P34HB (the electrospun scaffold and deposited film) and proved that the scaffold held better cellular performance in adipose-derived stem cells (ASCs). 28 Additionally, cellular behaviors on the deposited films and their capacity of in vivo cartilage regeneration were also evaluated and confirmed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biomimetic scaffolds using natural and synthetic biomaterials are highly desirable to recreate the micro‐architecture of articular cartilage. Some studies have suggested that environmental, cytokines and suitable scaffold materials can promote bone and cartilage tissue regeneration . Although intensive research has focused on the developmental biology and regeneration of cartilage tissue, and a diverse plethora of biomaterials have been developed for this purpose, cartilage regeneration is still suboptimal with disadvantages, such as lack of a layered structure, mechanical mismatch with native cartilage, and inadequate integration between native tissue and the implanted scaffold …”
Section: Discussionmentioning
confidence: 99%